2014
DOI: 10.1002/cbic.201402407
|View full text |Cite
|
Sign up to set email alerts
|

Generic Structures of Cytotoxic Liprotides: Nano‐Sized Complexes with Oleic Acid Cores and Shells of Disordered Proteins

Abstract: The cytotoxic complex formed between α-lactalbumin and oleic acid (OA) has inspired many studies on protein-fatty acid complexes, but structural insight remains sparse. After having used small-angle X-ray scattering (SAXS) to obtain structural information, we present a new, generic structural model of cytotoxic protein-oleic acid complexes, which we have termed liprotides (lipids and partially denatured proteins). Twelve liprotides formed from seven structurally unrelated proteins and prepared by different pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 54 publications
3
72
0
Order By: Relevance
“…Alpha-lactalbumin protein triggers cell death in normal rat intestinal epithelial cells (63) and virus-transformed mouse leukaemia cells (64). These results and HAMLET results showing HAMLET cytotoxicity superior to that of the oleic acid alone (3)(4)(5)15,17,38,44,50,54), indicate that α-lactalbumin protein is also playing role in HAMLET-induced cell death.…”
Section: Oleic Acid Is the Main Active Componentmentioning
confidence: 66%
See 4 more Smart Citations
“…Alpha-lactalbumin protein triggers cell death in normal rat intestinal epithelial cells (63) and virus-transformed mouse leukaemia cells (64). These results and HAMLET results showing HAMLET cytotoxicity superior to that of the oleic acid alone (3)(4)(5)15,17,38,44,50,54), indicate that α-lactalbumin protein is also playing role in HAMLET-induced cell death.…”
Section: Oleic Acid Is the Main Active Componentmentioning
confidence: 66%
“…Other studies found that the protein-lipid complex is more cytotoxic than similar amounts of oleic acid or sodium oleate alone (3)(4)(5)15,17,38,44,50,54). It is not yet clear whether these are true differences in cytotoxicity for the different protein carriers of oleate, or whether these different results reflect difficulties in solubilising oleic acid alone for delivery in water-based cellular systems, or are a result of accuracy and precision in measuring the oleate amounts present in the HAMLET-like compounds.…”
Section: Oleic Acid Is the Main Active Componentmentioning
confidence: 97%
See 3 more Smart Citations